Case report: Acute vestibular syndrome and cerebellitis in anti-Yo paraneoplastic syndrome - Kherallah, Bassil; Samaha, Elias; Bach, Sarah E.; Guede, Cindy; Kattah, Jorge C. (Frontiers in Neurology, 2022)
Background We define acute vestibular syndrome (AVS) as a sudden onset vertigo, nausea, vomiting, and head motion intolerance, more frequently associated with an acute peripheral and unilateral vestibulopathy. About 10–20% of all cases with central vestibulopathy are secondary to stroke. We report three patients evaluated over the past decade with an acute AVS along with subtle downbeat nystagmus (DBN), followed by dysarthria and progressive truncal and limb ataxia, as well as increasing DBN intensity. Methods All patients underwent neurologic examination, video-oculography, MRI, serum cancer markers, spinal fluid examination, paraneoplastic panel testing, and oncologic workup. With a consolidated diagnosis of cancer/paraneoplastic syndrome, we treated with plasma exchange (PLEX), high-dose steroids, surgery, and oncologic investigation. We additionally provided oncotherapy in one out of three patients. Results All three patients had an acute AVS, downbeat nystagmus DBN, and inability to perform tandem gait. Two of three patients had a normal head impulse test (HIT). As acute vertigo, nausea, and vomiting subsided, a progressive cerebellar syndrome ensued characterized by persistent DBN, impaired horizontal and vertical pursuit, impaired VOR suppression, truncal and limb ataxia, and dysarthria. All patients had normal MRI brain studies excluding stroke. CSF studies demonstrated lymphocytic pleocytosis and elevated protein. One patient had confirmed ovarian cancer with high CA-125 serum levels; another had undifferentiated cancer of unknown primary with high CA-125 and one patient with esophageal cancer. All had a positive PCA-1 antibody titer, also known as anti-Yo antibody. In one patient with expeditious immunosuppression, the ataxia progression slowed for 18 months, whereas the other two patients with delayed initiation of treatment had more rapidly progressive ataxia. Discussion Paraneoplastic encephalitis related to PCA-1 antibody (Anti-Yo) targets Purkinje cells and cells in the granular layer of the cerebellar cortex. Clinically, our patients had a central AVS characterized by DBN and followed with progressive ataxia and unremarkable neuroimaging studies. Rapid initiation of treatment may offer a greater chance to prevent further neurologic decline. Any patient with an AVS as well as DBN and normal MRI should have an expeditious workup to rule out metabolic, toxic, and infectious causes just prior to considering prompt treatment with high-dose steroids and plasma exchange (PLEX) to mitigate the risk of rapidly progressive and irreversible neurologic decline.